Aktualisasi Konsep Al-Mantuq dan Al-Mafhum Perspektif Usul Fiqih dalam Diskursus Penafsiran Al-Qur’an - Khusnul Khitam, Achmad (Qaf: Jurnal Ilmu Al-Qur'an dan Tafsir, 2023)
This article aims to discuss as well as actualize the concept of al-mantuq wa al-mafhum from the us}ul fiqh perspective in the discussion of Qur’anic interpretation. This article will focus on how Qur’anic interpretation can be approached by other discipline, namely usul fiqh, and how can the result of this approach be actualized in current situation. This Article is counted as library research, which is proceed by gathering some facts from various literatures related to the subject, and it uses analytic description method to discuss the subject. There are three main points that are found from this research: firstly, the concept of al-mantuq wa al-mafhum can be used to understand original meaning of the verse, secondly, the concept of al-mantuq wa al-mafhum can also be used to produce a new and contemporary meaning which is more suitable to current situation, and lastly, the production of those new contemporary meaning can be used as the basis of the production of law, which is known as istinbath al-hukm.